The Effect of Tax Literacy, Tax Justice, and Tax Law Enforcement on Non-Employee Taxpayer Compliance Through Tax Morale as an Intervening Variable - Anissa Yuniar Larasati; Bani Binekas (International Journal of Economics Development Research (IJEDR), 2023)
Taxes have an important role for Indonesia, one of the main functions of taxes is that taxes are a source of state revenue intended for the realization of the welfare and prosperity of the nation. Self Assessment System requires a change in attitude (awareness) of taxpayers to pay taxes voluntarily (voluntary compliance). Voluntary compliance with tax obligations is the backbone of the Self Assessment System. The high and low level of people's compliance in paying taxes is influenced by internal factors and also external factors. In this study, the internal factors that will be examined are tax literacy and tax morale factors, while the external factors studied are the variables of Tax Justice and Tax Law Enforcement. The research method used is to use descriptive research methods through a quantitative approach. The data collection technique used in this study, namely primary data. This study uses Path Analysis in testing data. Primary data obtained through questionnaire techniques distributed to 60 non-employee individual taxpayers in the Cibeunying Pratama KPP area. And will be tested using SPSS v.26. Based on the results of the path analysis test, it is known that tax literacy, tax justice, and tax law enforcement have no indirect effect on non-employee taxpayer compliance through tax morale at KPP Pratama Cibeunying.